Menilik Historitas Pembaruan Pendidikan Pesantren - Mahfud Ifendi (JP : JURNAL PENDIDIKAN, 2017)
In accordance with the incessant sound of renewal of Islamic thought reformers waged by Muslims from various countries of Egypt, India, Turkey to also echo the update to Indonesia. One of the effects of the "voice updates," it is the appearance of reform in the field of Islamic education. Boarding school as a base of Islamic education is the oldest educational centers in Indonesia because it is in line with the spread of Islam in Indonesia trip. Along with the dynamic development of science, the boarding school had to undergo changes towards modernity. The idea and the core of this update is to attempt to leave the old thought patterns that are not in accordance with the progress of the times and strive for sustaining aspects to adjust to the progress of time. Based on the two thrust that; so began to emerge the idea to include general subjects to Islamic educational institutions as well as change the old teaching methods to methods more adaptive to the times.Keywords; Modernity, Islamic Boarding School